A Review on the Role of Nicotine in Electronic Cigarettes and their Impact on Oral Tumorigenesis and Metastasis - Balasamy, Sesuraj; Sundramoorthy, Ashok K. (Micro and Nanosystems, 2025)
In this study, we have highlighted the examination of nicotine levels in both e-cigarettes and traditional cigarettes, elucidating their impact on tumorigenesis and metastasis. This review delves into the surging prevalence of e-cigarette usage, especially among young demographics, alongside the conflicting findings regarding their health effects. The passage explores the varied toxicological impacts of e-cigarettes, the intricate interplay between nicotine and cancer, and the comparative toxicity vis-à-vis traditional cigarettes. We noted nicotine's influence on accelerating metastasis, particularly focusing on its effects on Oral Squamous Cell Carcinomas (OSCCs). The clinical implications underscore the importance of understanding nicotine delivery kinetics for tailored interventions.
Keywords: Nicotine